Clinical manifestation of syphilis and serological conflictin coinfection with HIV - Oliveira, Felipe L; Benicio, Karen; Cerutti, Gisele; Natividade, Natallia B; Nery, José Augusto C (Brazilian Journal of Sexually Transmitted Diseases, 2011)
The nontreponemal serology have great value in the diagnosis of secondary syphilis, but the patients coinfected with human immunodeficiency virus may develop abnormal responses before antigenic stimulation and therefore produce false-negative serologic responses or some false-positive infections, including syphilis. Thus, clinicians should be alert to skin lesions suggestive of syphilis and proceed performing diagnostic tests, and not delay treatment to avoid further damage to the patient. This report assesses the conduct adopted front of the patient with symptoms suggestive of secondary syphilis with VDRL initially negative and HIV positive, developing, after the introduction of penicillin, increasing titers of VDRL